A two-in-one dual channel chemosensor for Fe3+ and Cu2+ with nanomolar detection mimicking the IMPLICATION logic gate. Issue 2 (24th November 2014) - Kuwar, Anil; Patil, Rahul; Singh, Amanpreet; Sahoo, Suban K.; Marek, Jaromir; Singh, Narinder
Abstract : A highly selective colorimetric as well as fluorescence sensor for Fe(iii ) and Cu(iii ) in 99% aqueous medium. Abstract : A novel and easy-to-synthesize colorimetric and fluorescent chemosensor1 was developed for the highly selective and sensitive recognition of Fe 3+ and Cu 2+ . Receptor1 showed a detectable color change from yellow to colorless with a blue-shift in the absorption spectra with Cu 2+, while Fe 3+ induced a color change from yellow to orange and a red-shift in the absorption spectra. In the emission study of1, Fe 3+ showed significant fluorescence enhancement with a slight red-shift while a selective fluorescence quenching was observed with Cu 2+ over a wide range of tested metal ions. With Cu 2+ /Fe 3+ as the chemical inputs, the 'on–off' emission profile of receptor1 was developed as an IMPLICATION type logic gate at the molecular level.